Pleomorphic adenoma of head and neck region: our institutional review - Singh, Gurbax; Prinja, Sumit; ., Aarushi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Pleomorphic adenoma is the commonest benign salivary gland neoplasm but it has the tendency to reoccur if not properly removed and has ability to undergo malignant transformation. The aim of the study was to discuss the presentation and treatment of pleomorphic adenoma of the head and neck region. Methods: Retrospective chart review of patients treated for pleomorphic adenoma of the head and neck region between 2011 and 2018. Data assessed included demographics, clinical presentation, imaging, treatment, complications, recurrence and follow‐up. Results: Seventy nine patients with pleomorphic adenoma were identified. Major salivary gland lesions were most common (n=64, 81.0%); 67% (53 of 64) arising in the parotid and 14% (11 of 64) in the submandibular glands. Minor salivary gland lesions were removed from the palate (8 of 15, 53.3%), parapharyngeal space (3 of 15, 20%), nasal septum (2 of 15, 13.3%), lower lip (1 of 15, 6.7%) and base of tongue (1 of 15, 6.7%). Preoperative imaging done was mainly computed tomography in all the cases however in parapharyngeal space cases magnetic resonance imaging was also done. Surgical excision was performed in all patients except base of tongue case. Conclusions: Treatment of pleomorphic adenoma is mainly surgical with negative margin. Rate of recurrence is low, however long follow-up is recommended.